Spiritual Activity and Socio Cultural Crisis of Personality - Mikailova, Narmina (Scholarya Demo Journal of Ruby, 2018)
The topic of the socio-cultural crisis is one of the actual problems of te modern world, and it is connected with the vision related to the inner richness of culture. The crisis of culture is the decay of a specific type of integrity; it is associated with the existential search of humans and their search for the ways of sociodynamics. The modern socio-cultural crisis foreshadows a new cultural paradigm. Modern science offers several options for resolving the crisis of culture, one of which is the inner spiritual self-perfection of man. The growth of the spirituality of the individual implies the acquisition of a rich spiritual content by it, spirituality is a way of self-identification of a person. Spirituality is the force that directs all human activity, its stimulus. The sphere of spirituality is the human essence and human content, it contains the system of a person’s rich social experience. At the same time, spirituality reveals the degree of individuality of a person. The way out of the crisis is the growth of the spirituality of a person as a free subject. The greatest degree of his activity, his creative-creative potential is manifested in the spirituality of a person. The preservation of the spiritual activity of the individual is promoted by creative activity, which is the driving force of culture.